Wall conditioning and ELM mitigation with boron nitride powder injection in KSTAR. (September 2021) - Gilson, E.P.; Lee, H.H.; Bortolon, A.; Choe, W.; Diallo, A.; Hong, S.H.; Lee, H.M.; Lee, J.; Maingi, R.; Mansfield, D.K.; Nagy, A.; Park, S.H.; et al.
Abstract: Results from KSTAR powder injection experiments, in which tens of milligrams of boron nitride (BN) were dropped into low-power H-mode plasmas, show an improvement in wall conditions in subsequent discharges and, in some cases, a reduction or elimination of edge-localized modes (ELMs). Injected powder is distributed by the plasma flow and is deposited on the wall and, over the course of several discharges, was observed to gradually reduce recycling by 33%, and decrease both the ELM amplitude and frequency. This is the first demonstration of the use of BN for ELM mitigation. In all of these experiments, an Impurity Powder Dropper (IPD) was used to introduce precise, controllable amounts of the materials into ELMy H-mode KSTAR discharges. The plasma duration was between 10 s and 15 s, I p = 500  kA, B T = 1 . 8  T, P NBI = 1 . 6  MW, and P ECH = 0 . 6  MW. Plasma densities were between 2 and 3 × 1 0 19  m −3 . In all cases, the pre-fill and startup gas-fueling was kept constant, suggesting that the decrease in baseline D α emission is in fact due to a reduction in recycling. The results presented herein highlight the viability of powder injection for intra-shot and between-shot wall conditioning. Highlights: Impurity powder dropper used to drop boron nitride into KSTAR plasmas. Boron nitride reduces wall recycling. Boron nitride leads to reduced ELM amplitude and frequency. Boron nitride also leads to ELM-free phases.